2015
DOI: 10.1080/07448481.2015.1015030
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing a Cognitive-Behavioral Protocol on Psychosocial Predictors of Exercise, Nutrition, Weight, and Body Satisfaction Changes in a College-Level Health-Related Fitness Course

Abstract: Overall, results were positive and warrant more comprehensive testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…Table summarizes study characteristics, while Table S2 tabulates detailed study characteristics. Of the 51 included studies, 20 studies were eligible for meta‐analysis of BMI, 19 studies were eligible for meta‐analysis of weight, and 10 studies were eligible for meta‐analysis of waist circumference …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table summarizes study characteristics, while Table S2 tabulates detailed study characteristics. Of the 51 included studies, 20 studies were eligible for meta‐analysis of BMI, 19 studies were eligible for meta‐analysis of weight, and 10 studies were eligible for meta‐analysis of waist circumference …”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 studies measured changed in BMI, with 32 of these using an objective measure for BMI, while four studies used self‐report measures for BMI . This includes the 20 studies from the meta‐analysis and a further 16 studies that reported BMI as an outcome, but results were not comparable and therefore not included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women with self-reported goals for reducing weight by improving physical activity and nutritional behaviours, whose data were extracted from data sets associated with previous research (Annesi, 2017;Annesi & Gorjala, 2010;Annesi, Howton, Johnson, & Porter, 2015), were participants. Other inclusion criteria were as follows: (1) no physical contraindication for participation, (2) no current participation in a weight management programme, (3) not meeting the current minimum recommended volume of physical activity of 150 min/week of moderate activity (Garber et al, 2011), and (4) not presently pregnant or planning to soon become pregnant.…”
Section: Participantsmentioning
confidence: 99%